Ipazia d’Alessandria come anello della grande tradizione filosofica greca. Μῆτερ καὶ ἀδελφὴ καὶ διδάσκαλε (Itinera, 2012)
In this paper we are moving from the analysis of the historiographical and literary aspects of the figure of Hypatia of Alexandria in order to get to the reconstruction of her personal and intellectual trajectory. We enunciate the guidelines of her thought, which we base on her methodological approach to mathematics, geometry and astronomy; on the basic beliefs of the cosmological model to which she would have given her support; and finally, on the global vision which defines her manner of philosophizing as search for theoretical unity as well as practical engagement.